Peningkatan Kemampuan Literasi dan Numerasi Peserta Didik Melalui Program Kampus Mengajar Angkatan 2 - Bagus Ali Rachman; Firyalita Sarah Firdaus; Nurul Lailatul Mufidah; Halimatus Sadiyah; Ifit Novita Sari (Universitas Lancang Kuning, 2021)
This service is motivated by the activities of Campus Teaching 2 which is a form of implementation of the Merdeka Learning Campus Merdeka (MBKM) program from the Ministry of Education, Culture, Research and Technology. This program is based on the ineffectiveness of the implementation of learning carried out during the Covid-19 pandemic. This can be seen from the decline in students' interest in learning, the level of understanding of students when learning, and the literacy and numeracy abilities of students. Based on these problems affect the effectiveness of the learning process, one of which is in SMP Negeri 2 Tanggulangin. One of the methods used in the service is literacy and numeracy habituation activities. The final result of this activity is the habituation of literacy and numeracy for students at SMP Negeri 2 Tanggulangin and increasing the real role and contribution of higher education institutions and students in national development